Searching the chemical space of hetero-atom bridged norbornadienes - Oberhof, Nils; Hillers-Bendtsen, Andreas Erbs; Obel, Oscar Berlin; Schjelde, Karoline; Mikkelsen, Kurt V.; Dreuw, Andreas (Physical chemistry, chemical physics, 2025)
The efficient utilization of solar energy as renewable source is a central pillar of societal future energy production. So-called molecular solar thermal energy storage (MOST) systems have attracted considerable attention as storage solution and heat release on demand. Substituted norbornadiene/quadricyclane (NBD/QC) derivatives have been shown to be well suited for this task, in particular when substituted with electron donating and accepting functional groups. The introduction of a hetero-atom in the main structural framework, however, has not been investigated thoroughly, yet. In this study, a previously established high-throughput screening procedure is used to investigate carbon, nitrogen and oxygen-bridged norbornadiene derivatives for their potential as MOST system employing their theoretical solar power conversion efficiency as scoring metric. Therefore, we explore a large chemical space considering also plausible synthetic availability and propose a set of 5 molecules per bridge head as best candidates for further experimental evaluation.